Quality of eggs packaged in different types of packaging and stored in commercialization stations in the Municipality of São João del - Rei , MG (Research, Society and Development, 2020)
The objective of this study was to evaluate the quality of eggs packaged in different types of packaging and stored at marketing stations in the municipality of São João del-Rei, over 35 days. 360 white eggs from Hy Line W36 liners were used, distributed in a completely randomized experimental design in a 2x3x5 factorial scheme (two storage locations / supermarkets (S1 and S2), 3 types of packaging (Styrofoam (Iso), plastic (Plas ) and cellulose (Cel)) and five evaluation periods: 7, 14, 21, 28 and 35 days), totaling 30 treatments with four repetitions, consisting of 3 eggs each. The data obtained for each parameter were subjected to analysis of variance, adopting a significance level of 5%. In case of statistical significance (P